Systematic Literature Review untuk Membuat Model Aplikasi Pemantauan Kesehatan Cardiovascular - Muhammad Sobri; Mohammad Taha Ijab; Norshita Mat Nayan (Jurnal RESTI (Rekayasa Sistem dan Teknologi Informasi), 2018)
Human Computer Interaction (HCI) research and in particular usability aspects for cardiovascular disease (CVD) health monitoring application in the developing countries have been an underresearch phenomenon. In the era of digitization, heart patients are relying more on cardiovascular disease (CVD) health monitoring applications on mobile devices to monitor their hearts’ conditions. In order for the applications to be usable by the CVD patients, several usability aspects such as ease of use, learnability, effectiveness, flexibility and attitude of users are imperative in determining the usability of the applications. This research investigates the integration of usability aspects into CVD health monitoring application by usability engineers and system developers. This research employs Systematic Literature Review (SLR) method on usability aspects of CVD health monitoring applications. This research proposes a conceptual model called the Usability of Cardiovascular Health Monitoring Application Model (uCALM). The model aims to improve the usability aspects of CVD health monitoring application for the benefits of the patients and their cardiologists.